Biosynthesized Silver Nanoparticles by Aqueous Stem Extract of Entada spiralis and Screening of Their Biomedical Activity - Wan Mat Khalir, Wan Khaima Azira; Shameli, Kamyar; Jazayeri, Seyed Davoud; Othman, Nor Azizi; Che Jusoh, Nurfatehah Wahyuny; Hassan, Norazian Mohd (Frontiers in Chemistry, 2020)
Silver nanoparticles (Ag-NPs) have been established as antibacterial nanoparticles and innovatively developed to overcome the occurrence of antibiotic resistance in the environment. In this study, an environmentally friendly and easy method of biosynthesis of Ag-NPs plant mediated by aqueous extract stem extract of Entada spiralis (E. spiralis) was successfully developed. The E. spiralis/Ag-NPs samples were characterized using spectroscopy and microscopic technique of UV-visible, XRD, FETEM, SEM, EDX, zeta potential and FTIR analyses. Surface Plasmon Resonance (SPR) absorption at 400-450 nm in the UV-visible spectra established the formation of E. spiralis/Ag-NPs. The crystalline structure of E. spiralis/Ag-NPs was displayed in the XRD analysis. The small size around 18.49 ± 4.23 nm and spherical shape of Ag-NPs with good distribution was observed in FETEM image. The SEM and EDX images exhibit a good distribution of Ag-NPs on the E. spiralis extract surface and a high percentage of Ag (79.93%) element appeared at 3.0 keV. The best physicochemical parameters on Ag-NPs biosynthesis using E. spiralis extract occurred at moderate temperature (~52.0 °C), 0.100 M of silver nitrate, 2.50 g of E. spiralis dosage and 600 min of stirring reaction time. The antibacterial activity was tested against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli and Proteus vulgaris using antibacterial disk diffusion assay. Based on the results, it is evident that E. spiralis/Ag-NPs are susceptible to all the bacteria and potentially promising to be applied in both industry and medical fields.